EMU and the International Monetary System. (International Monetary Fund, 1997)
This book, edited by Paul R. Masson, Thomas Krueger, and Bart G. Turtelboom, contains the proceedings of the seminar held in Washington, D.C. on March 17-18, 1997, cosponsored by the IMF and Fondation Camille Gutt. Conference participants discussed implications of European Economic and Monetary Union (EMU) on exchange and financial markets, and consequently on the activities of market participants and private and official institutions. The five main themes of the seminar were the characteristics of the euro and its potential role as an international currency; EMU and international policy coordination; EMU and the relationship between the IMF and its EMU members; lessons of European monetary integration for the international monetary system; and the transitioin to EMU.